Statin therapy and thromboxane generation in patients with coronary artery disease treated with high-dose aspirin - Bliden, Kevin P.; Singla, Anand; Gesheff, Martin G.; Toth, Peter P.; Tabrizchi, Ali; Ens, Gordon; Guyer, Kirk; Singh, Mandeep; Franzese, Christopher J.; Stapleton, Dwight D.; Tantry, Udaya S.; Gurbel, Paul A. (Thrombosis and Haemostasis, 2014)
Aspirin and statin therapy are mainstay treatments in patients with coronary artery disease (CAD). The relation between statin therapy, in vivo thromboxane (Tx) generation; a marker of inflammation, and blood thrombogenicity has never been explored. Urinary 11-dehydro (dh) TxB2 was determined in patients with suspected CAD on 325 mg daily aspirin therapy prior to undergoing cardiac catheterisation (n=281). Thrombogenicity was estimated by thrombelastographic measurement of thrombin-induced platelet-fibrin clot strength (TIP-FCS) and lipids/lipoproteins were determined by vertical density gradient ultracentrifugation/ELISA. The influence of statin therapy and dose was analysed by the atorvastatin equivalent dose (5–10 mg, 20–40 mg, or 80 mg daily). Statin therapy (n=186) was associated with a dose-dependent reduction in urinary 11-dh TxB2 (p=0.046) that was independent of LDL and apo B100 levels but was strongly related to TIP-FCS (p=0.006). By multivariate analysis, no statin therapy (n=95) and female gender were independently associated with high urinary 11-dh TxB2 [OR=2.95 (0.1.57–5.50, p=0.0007); OR=2.25 (1.24–4.05, p=0.007)], respectively. In aspirin-treated patients, statin therapy was independently and inversely associated with inflammation in a dose-dependent manner. Elevated 11-dh TxB2 was associated with a prothrombotic state indicated by high TIP-FCS. Our data suggest that measurement of urinary 11-dTxB2 may be a useful method to optimise statin dosing in order to reduce thrombotic risk.
Keywords: Aspirin; statin; urinary 11-dehydrothromboxane B2; lipids; inflammation; coronary artery disease; platelets